Structural Response of Irregular Buildings: Influence of Geometry and Shear Wall Configurations - Teguh, Mochamad; Pratama, Aditia Ilham (Universitas Negeri Semarang, 2025)
This paper delves into the structural response of irregular buildings, specifically focusing on the influence of geometry and shear wall configurations. Irregular buildings, with their intricate geometries and diverse structural elements, present unique design challenges, necessitating a thorough performance evaluation. Our study conducts a comparative analysis to gauge the impact of various geometric layouts and shear wall arrangements on structural behavior under seismic loading. A nine-story irregular building in Yogyakarta, Indonesia, is a compelling case study. We develop three models (M1, M2, and M3), each incorporating variations in geometry and shear wall configurations (T-shaped, L-shaped, and I-shaped). These models are rigorously analyzed using ETABS software to evaluate key structural responses, including lateral displacement, inter-story drift, and base shear forces. The results reveal that M3 exhibits the lowest base shear, at 24,961.46 kN, 7.582% lower than the existing model (M1). The lowest lateral displacements and inter-story drifts are observed in the x-direction for M2 (26.308 mm displacement, 10.061 mm drift) and in the y-direction for M3 (26.115 mm displacement, 9.339 mm drift). Additionally, the lowest drift ratio occurs on the first floor of M3, measuring 0.110% in the x-direction and 0.115% in the y-direction. These findings underscore the substantial impact of geometric variations and shear wall configurations on the structural response, providing valuable insights into optimizing irregular building designs to enhance seismic performance.